Flagella-Associated WDR-Containing Protein CrFAP89 Regulates Growth and Lipid Accumulation in Chlamydomonas reinhardtii - Luo, Qiulan; Song, Wenwen; Li, Yajun; Wang, Chaogang; Hu, Zhangli (Frontiers in Plant Science, 2018)
WD40-repeat (WDR) domain-containing proteins are subunits of multi-protein E3 ligase complexes regulating various cellular and developmental activities in eukaryotes. Chlamydomonas reinhardtii serves as a model organism to study lipid metabolism in microalgae. Under nutrition deficient conditions, C. reinhardtii accumulates lipids for survival. The proteins in C. reinhardtii flagella have diverse functions, such as controlling the motility and cell cycle, and environment sensing. Here, we characterized the function of CrFAP89, a flagella-associated WDR-containing protein, which was identified from C. reinhardtii nitrogen deficiency transcriptome analysis. Quantitative real time-PCR showed that the transcription levels of CrFAP89 were significantly enhanced upon nutrient deprivation, including nitrogen, sulfur, or iron starvation, which is considered an effective condition to promote triacylglycerol (TAG) accumulation in microalgae. Under sulfur starvation, the expression of CrFAP89 was 32.2-fold higher than the control. Furthermore, two lines of RNAi mutants of CrFAP89 were generated by transformation, with gene silencing of 24.9% and 16.4%, respectively. Inhibiting the expression of the CrFAP89 gene drastically increased cell density by 112%-125% and resulted in larger cells, that more tolerant to nutrition starvation. However, the content of neutral lipids declined by 12.8%-19.6%. The fatty acid content in the transgenic algae decreased by 12.4% and 13.3%, mostly decreasing the content of C16:0, C16:4, C18, and C20:1 fatty acids, while the C16:1 fatty acid in the CrFAP89 RNAi lines increased by 238.5% to 318.5%. Suppressed expression of TAG biosynthesis-related genes, such as CrDGAT1 and CrDGTTs, were detected in CrFAP89 gene silencing cells, with a reduction of 16%-78%. Overall our results suggest that down-regulating of the expression of CrFAP89 in C. reinhardtii, resulting in an increase of cell growth and a decrease of fatty acid synthesis with the most significant decrease occurring in C16:0, C16:4, C18 and C20:1 fatty acid. CrFAP89 might be a regulator for lipid accumulation in C. reinhardtii.